2020
DOI: 10.1101/2020.03.20.000117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Irish potato famine pathogen subverts host vesicle trafficking to channel starvation-induced autophagy to the pathogen interface

Abstract: Eukaryotic cells deploy autophagy to eliminate invading microbes. In turn, pathogens have evolved 22 effector proteins to counteract antimicrobial autophagy. How and why adapted pathogens co-opt 23 autophagy for their own benefit is poorly understood. The Irish famine pathogen Phythophthora 24 infestans secretes the effector protein PexRD54 that selectively activates an unknown plant 25 autophagy pathway, while antagonizing antimicrobial autophagy. Here we show that PexRD54 26 induces autophagosome formation b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…PexRD54 was also recently proposed to connect small GTPase Rab8a vesicles with the autophagy machinery to stimulate formation of autophagosomes at the pathogen interface (Pandey et al, 2020). In our host-interactor screen, we found that ten effector families associated with 32 proteins implicated in vesicle mediated transport ( Figure 2, Figure S3, Table S2).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…PexRD54 was also recently proposed to connect small GTPase Rab8a vesicles with the autophagy machinery to stimulate formation of autophagosomes at the pathogen interface (Pandey et al, 2020). In our host-interactor screen, we found that ten effector families associated with 32 proteins implicated in vesicle mediated transport ( Figure 2, Figure S3, Table S2).…”
Section: Discussionmentioning
confidence: 72%
“…binding (Pandey et al, 2020). The PexRD54 work illustrates the importance of replication and follow-up experiments to the coIP/MS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reason behind this is not understood. Recently, it has been revealed that PexRD54 imitates starvation conditions and serves as a receptor for recruiting the small GTPase Rab8a with a role in basal resistance against P. infestans , and the lipid droplets (LDs) associated with Rab8a to form a distinct LDs-Rab8a-PexRD54-ATG8CL autophagosomes [ 113 ] ( Figure 2 ). As a result, the Rab8a is trapped inside the autophagosomes and the Rab8a-mediated basal immunity is pacified [ 113 ] ( Figure 2 ).…”
Section: Selective Autophagy—a Battlefield Between Plant–pathogen mentioning
confidence: 99%